Physiological cell bioprinting density in human bone-derived cell-laden scaffolds enhances matrix mineralization rate and stiffness under dynamic loading - de Leeuw, Anke M.; Graf, Reto; Lim, Pei Jin; Zhang, Jianhua; Schädli, Gian Nutal; Peterhans, Sheila; Rohrbach, Marianne; Giunta, Cecilia; Rüger, Matthias; Rubert, Marina; Müller, Ralph (Frontiers in Bioengineering and Biotechnology, 2024)
Human organotypic bone models are an emerging technology that replicate bone physiology and mechanobiology for comprehensive in vitro experimentation over prolonged periods of time. Recently, we introduced a mineralized bone model based on 3D bioprinted cell-laden alginate-gelatin-graphene oxide hydrogels cultured under dynamic loading using commercially available human mesenchymal stem cells. In the present study, we created cell-laden scaffolds from primary human osteoblasts isolated from surgical waste material and investigated the effects of a previously reported optimal cell printing density (5x10 6 cells/ml bioink) vs. a higher physiological cell density (10x10 6 cells/ml bioink).We studied mineral formation, scaffold stiffness, and cell morphology over a 10-week period to determine culture conditions for primary human bone cells in this microenvironment. For analysis, the human bone-derived cell-laden scaffolds underwent multiscale assessment at specific timepoints. High cell viability was observed in both groups after bioprinting (>90%) and after 2 weeks of daily mechanical loading (>85%). Bioprinting at a higher cell density resulted in faster mineral formation rates, higher mineral densities and remarkably a 10-fold increase in stiffness compared to a modest 2fold increase in the lower printing density group. In addition, physiological cell bioprinting densities positively impacted cell spreading and formation of dendritic interconnections. We conclude that our methodology of processing patient-specific human bone cells, subsequent biofabrication and dynamic culturing reliably affords mineralized cell-laden scaffolds. In the future, in vitro systems based on patient-derived cells could be applied to study the individual phenotype of bone disorders such as osteogenesis imperfecta and aid clinical decision making.